Serious Gaming as an Additional Learning Tool for Medical Education - Aksoy, Mehmet E.; Sayali, Mehmet E. (International Journal of Educational Technology and Learning, 2019)
Computer-based learning methodologies have become more prevalent in the last decade. Web-based serious gaming and virtual patients are novel in medical education, which has the potential to become important tools to improve today’s medical students’ knowledge and performance. A total of 81 medical students participated in our study. They were either assigned to an intervention group or a control group. The intervention group completed a serious game module designed for Basic Life Support education. The control group received a theoretical lecture on the same content. On the next day, both groups received simulation-based hands-on training for BLS using the same criteria. All students were assessed with an Objective Structured Clinical Examination (OSCE) the following week. There was no difference between the intervention group using a web-based serious game module for BLS and the control group that received a standard theoretical lecture from the faculty. Computer-based interactive serious games seem to present a favourable additional tool for medical education. OSCE results imply, that the use of serious games as a self-learning strategy can be as useful as theoretical lectures; which means that it is saving the time of learners and educators.